SIRT3 Protects Against Acute Kidney Injury via AMPK/mTOR-Regulated Autophagy - Zhao, Wenyu; Zhang, Lei; Chen, Rui; Lu, Hanlan; Sui, Mingxing; Zhu, Youhua; Zeng, Li (Frontiers in Physiology, 2018)
Acute kidney injury (AKI), which involves the loss of kidney function caused by damage to renal tubular cells, is an important public health concern. We previously showed that sirtuin (SIRT)3 protects the kidneys against mitochondrial damage by inhibiting the nucleotide-binding domain (NOD)-like receptor protein 3 (NLRP3) inflammasome, attenuating oxidative stress, and downregulating proinflammatory cytokines. In this article, we investigated the role of autophagy, mediated by a mammalian target of rapamycin (mTOR) and AMP-activated protein kinase (AMPK), in the protective effect of SIRT3, against sepsis-induced AKI, in a mouse model of cecal ligation and puncture (CLP). The AKI in CLP mice was associated with the upregulation of autophagy markers; this effect was abolished in SIRT3− mice in parallel with the downregulation of phospho (p)-AMPK and the upregulation of p-mTOR. Pretreatment with the autophagy inhibitor 3-methyladenine (3-MA) or AMPK inhibitor compound isotonic saline (C), exacerbated AKI. SIRT3 overexpression promoted autophagy, upregulated p-AMPK and downregulated p-mTOR in CLP mice, attenuating sepsis-induced AKI, tubular cell apoptosis, and inflammatory cytokine accumulation in the kidneys. The blockage of autophagy induction largely abolished the protective effect of SIRT3 in sepsis-induced AKI. These findings indicate that SIRT3 protects against CLP-induced AKI by inducing autophagy through regulation of the AMPK/mTOR pathway.